The demand for a dengue vaccine: A contingent valuation survey in Metro Manila - Palanca-Tan, Rosalina (Archīum Ateneo, 2008)
Using data gathered from a contingent valuation survey, this study estimated the willingness to pay (WTP) for a single dengue fever vaccine and the household demand function for dengue vaccines. Mean WTP for the vaccine ranged from US$27 to US$32 and household demand averaged 2 per household. Our findings indicate sufficiently high WTP for dengue vaccines and hence a significant potential for selling the vaccine in private markets. For the lower income groups with lower capacity to pay, a mass vaccination campaign program in which part of the financial costs are covered by vaccine user charges is viable.